2021
DOI: 10.1002/acp.3856
|View full text |Cite
|
Sign up to set email alerts
|

Does writing enhance recall and memory consolidation? Revealing the factor of effectiveness of the self‐administered interview

Abstract: Summary The self‐administered interview (SAI©) is a booklet in which eyewitnesses write down their memories of an incident without assistance. The SAI can gather a significant amount of eyewitness information, and completing the SAI soon after witnessing an event can improve later recall. This study aimed to reveal the factor of effectiveness of the SAI and specifically focused on the method of handwriting. Participants watched a video and immediately recalled the event in the three conditions: SAI‐writing, SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…They found that witnesses preferred giving spoken responses (as opposed to handwritten responses) and that those spoken responses, both in the immediate and in the one‐week delay conditions, were as accurate as handwritten responses. Miura and Matsuo (2021), however, found evidence of superior recall of correct details about a mock crime video (i.e., the same car theft video used in Gabbert et al, 2009) in SAI written conditions relative to SAI spoken conditions or spoken free recall conditions both immediately after viewing the video and when interviewed about 1 week later.…”
Section: Current Researchmentioning
confidence: 98%
“…They found that witnesses preferred giving spoken responses (as opposed to handwritten responses) and that those spoken responses, both in the immediate and in the one‐week delay conditions, were as accurate as handwritten responses. Miura and Matsuo (2021), however, found evidence of superior recall of correct details about a mock crime video (i.e., the same car theft video used in Gabbert et al, 2009) in SAI written conditions relative to SAI spoken conditions or spoken free recall conditions both immediately after viewing the video and when interviewed about 1 week later.…”
Section: Current Researchmentioning
confidence: 98%
“…While these correlations in combination with the predictions of encoding specificity theory (Tulving & Thomson, 1973) might imply that MRC would increase the sense of vividness, reliving, and belief compared with a simple free recall, we have yet to establish whether this is in fact the case, and whether phenomenological memory characteristics are associated with objective retrieval accuracy. In fact, free recall responses themselves may contain internal, idiosyncratic details and metacognitive statements (Diamond et al, 2020), and while such unverifiable, subjective statements are often omitted from accuracy coding of written recall (e.g., Gabbert et al, 2009;Hope et al, 2014;Miura & Matsuo, 2021;Pfeil, 2018), the occurrence of unverifiable details may provide further insight into the private perception of the remembered event.…”
Section: Mental Reinstatement Of Context and Subjective Characteristi...mentioning
confidence: 99%